2018
DOI: 10.24867/atm-2018-1-005
|View full text |Cite
|
Sign up to set email alerts
|

Improvements and materials for production of a magnetic drive micropump: an overview and recommendations

Abstract: This paper presents an overview of an improved solution for an existing micropump model and, also, of the materials recommended to be used in the current stage of the prototype research. This micropump is provided with a closed system for driving and pumping the fluid, obtained by a special constructive solution, where the rotation of the motor shaft is provided by induction of a magnetic field. The micropump system is composed by an external driving and an internal driven magnet, connected to a pair of gears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…In our research project, the constructive and functional parameters of a corrected gear solution are calculated through mathematical method and then used in a 3D parametric modeling. This led us to a first micropump solution presented in a previous paper [3]. Further research has been done to reduce the occurrence of wear on certain components of the micropump.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our research project, the constructive and functional parameters of a corrected gear solution are calculated through mathematical method and then used in a 3D parametric modeling. This led us to a first micropump solution presented in a previous paper [3]. Further research has been done to reduce the occurrence of wear on certain components of the micropump.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to improve the relative displacement and reduce the overall volume of the micropump, an innovative three-gear variant was designed. Through calculations and based on literature review [2,3,4] we concluded that displacement of the mixed fluid (flow) of the three-gear micropump is double compared with the previous solution, still in use in many applications in industry.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations